PRODUÇÃO DE HORTALIÇAS COM UTILIZAÇÃO DE BANCADA DE CULTIVO HIDROPÔNICO DE BAIXO CUSTO - ARAÚJO, Thales Oliveira; SERON, Cassio de Castro; VENDRUSCOLO, Eduardo Pradi; MARTINS, Murilo Battistuzzi; SILVA FILHO, Marcelo Xavier; LEONEL, Eduardo Augusto Souza (ANAIS DO ENIC, 2024)
-